The social origins of gender differences in anticipated feelings of guilt and shame following delinquency - De Boeck, Arne (Criminology & criminal justice, 2018)
In this study, we investigate gender differences in adolescents’ anticipated feelings of guilt and shame for engaging in shoplifting and retaliatory violence. More specifically, we examine the extent to which interpersonal relations with parents and teachers, perceived peer delinquency and traditional gender role beliefs have different effects on levels of shame-guilt among males and females, and to what extent these variables mediate gender differences in shame-guilt. We use data collected in a sample of 852 adolescents in Genk, a multi-ethnic city in the north-east of Belgium. Our findings confirm those of earlier research indicating that females experience a considerably higher threat of shame-guilt for engaging in delinquency than males. Factors explaining males’ and females’ anticipated shame-guilt feelings are similar in the case of shoplifting, but different in the case of violence. Differential exposure to peer delinquency and parental follow-up partially mediate the effect of gender on shame-guilt for engaging in shoplifting. Among males, endorsement of traditional masculinity predicts lower levels of shame-guilt for engaging in shoplifting and violence. Among females, endorsement of traditional femininity predicts lower levels of shame-guilt for engaging in shoplifting, but has no effect on shame-guilt for engaging in violence. We discuss the implications of our findings for understanding the contribution of shame-guilt to the social control of delinquency across gender.